Silicon/TiO2 core-shell nanopillar photoanodes for enhanced photoelectrochemical water oxidation. (21st December 2017) - Pavlenko, Mykola; Siuzdak, Katarzyna; Coy, Emerson; Jancelewicz, Mariusz; Jurga, Stefan; Iatsunskyi, Igor
Abstract: Nanostructured Si/TiO2 core-shell nanopillar (NP) photoanodes were synthesized to overcome photodegradation stability of Si and to enhance the efficiency for photoelectrochemical water splitting. The core-shell structures were fabricated by atomic layer deposition of TiO2 onto Si nanopillars synthesized by metal-assisted chemical etching and nanosphere lithography. Scanning electron microscopy, transmission electron microscopy, Raman and reflectance spectroscopies were utilized to characterize fabricated photoanodes. The obtained Si/TiO2 core-shell NP arrays exhibit less than 6% of optical reflectance in UV and visible region, providing good optical absorption. Photoelectrochemical (PEC) water oxidation of fabricated photoanodes was studied. We showed that n-Si/n-TiO2 NP exhibited a larger photocurrent than p-Si/n-TiO2 due to a barrier at the heterojunction. Optimal morphological parameter of Si/TiO2 NP for enhanced PEC water splitting were found. We demonstrated its enhanced PEC performance with a photocurrent density of 1.5 mA/cm 2 under simulated solar radiation with intensity of 100 mW/cm 2 . The relationship between the PEC performance and the electrolyte pH was also discussed. The design of the geometry of Si/TiO2 core-shell NP arrays offers a new approach for preparing stable and highly efficient photoanodes for PEC water splitting. Graphical abstract: Highlights: Si/TiO2 nanopillars core-shell array is prepared with a MACE and ALD methods. TiO2 /Si NP photoanodes exhibit enhanced photoactivity for water splitting. A maximum photocurrent density of TiO2 /Si NP photoanodes achieves to 1.5 mA/cm −2 vs. RHE. High performance due to enhanced light absorption efficiency and reduced charge recombination. TiO2 /Si NP photoanodes shows better photostability in different electrolytes.